Lectotypification of Phillipsia straminea (Sarcoscyphaceae, Ascomycota), an extinct fungus from Chichijima Island, Ogasawara Islands - Tochihara, Yukito; Kobayashi, Takahito; Shutoh, Kohtaroh (Phytotaxa, 2026)
Phillipsia straminea has not been reported since its original description from Chichijima Island in 1937. Examination of the Fungal Herbarium of the Hokkaido University Museum, Hokkaido University located specimens corresponding to the original materials, and one specimen was designated as the lectotype. Morphological observations of the lectotype clarified its diagnostic features, supporting its distinction from related species.